Alkali metal oxide and hydroxide reduction in thin films by ectopic surface passivation layers
By constructing a multilayer passivation layer SEI film stack on the lithium electrode in situ, the problem of dendrite growth during the charging and discharging process of lithium-ion batteries is solved, achieving efficient lithium-ion exchange and improved battery safety.
Patent Information
- Application Number
- CN202380079895.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-28
- Filing Date
- 2023-09-28
- Publication Date
- 2025-12-30
AI Technical Summary
Existing lithium-ion batteries are prone to forming dendrites during charging and discharging, which can lead to short circuits, overheating, and explosions. Furthermore, their cycle performance is insufficient, failing to meet the demands for high capacity and fast charging.
A stable solid electrolyte interface (SEI) film stack is constructed ex-situ on the lithium electrode. By treating the lithium film surface to form LiF and Li2S portions, the thickness of the SEI film is controlled to suppress dendrite growth. A multilayer passivation layer structure is adopted to improve lithium ion exchange efficiency.
It improves the cycle performance and charging speed of lithium metal batteries, reduces internal resistance, and enhances battery safety and stability.
Smart Images

Figure CN121241447A_ABST
Abstract
Description
background Technical Field
[0001] The embodiments disclosed herein are generally related to metal electrodes, and more specifically, to lithium-containing electrodes and high-performance electrochemical components (such as secondary batteries), including the lithium-containing electrodes and their manufacturing methods described above.
[0002] Related technical specifications
[0003] Rechargeable electrochemical energy storage systems are becoming increasingly important in many areas of daily life. High-capacity energy storage elements, such as lithium-ion (Li-ion) batteries and capacitors, are being widely used in a growing number of fields, including portable electronic devices, medical applications, transportation, large-scale grid-connected energy storage, renewable energy storage, and uninterruptible power supplies (UPS). In these applications, the charge / discharge time and capacity of the energy storage elements are critical parameters. Furthermore, the size, weight, and / or cost of these energy storage elements are also important parameters. Additionally, low internal resistance is beneficial for high performance. The lower the resistance, the fewer limitations the energy storage element encounters when supplying electrical energy. For example, in the case of batteries, internal resistance affects performance by reducing the total amount of useful energy stored in the battery and its ability to provide high current.
[0004] Lithium-ion batteries are considered the most likely to achieve the required capacity and cycle life. However, existing lithium-ion batteries typically lack the energy capacity and charge / discharge cycle life required for these growing applications.
[0005] Therefore, the market needs energy storage elements with faster charging, higher capacity, and improved cycle performance, which can also be manufactured more cost-effectively. There is also a need for components of energy storage elements that can reduce the internal resistance of the storage element. Summary of the Invention
[0006] In one embodiment, an anode for a battery is disclosed. The anode includes a substrate, a metal film on the substrate, and a solid electrolyte interface (SEI) film stack on the metal film. The SEI film stack includes a first passivation layer on the metal film and a second passivation layer on the first passivation layer.
[0007] In another embodiment, an energy storage element is disclosed. The energy storage element includes a cathode, an isolation membrane, and an anode. The cathode includes a cathode current collector and a cathode film located on the cathode current collector. The isolation membrane is located on the cathode film. The anode is located on the isolation membrane. The anode includes an anode film located on the isolation membrane, a solid electrolyte interface (SEI) membrane stack located on the anode film, and an anode current collector located on the anode film. The SEI membrane stack includes a first passivation layer located on the anode film and a second passivation layer located on the first passivation layer.
[0008] In another aspect, a method for forming a battery anode is disclosed. This method includes placing a metal film over a substrate and placing a solid electrolyte interface (SEI) membrane stack over the metal film. The process of placing the SEI membrane stack includes placing a first membrane over the metal film and placing a second membrane over the first membrane. The first membrane is a lithium carbonate membrane. The second membrane is a lithium halide membrane. Attached Figure Description
[0009] To enable a detailed understanding of the features of this disclosure mentioned above, reference can be made to embodiments, some of which are illustrated in the accompanying drawings. However, it is important to note that the drawings only show exemplary embodiments and should not be construed as limiting the scope, as the disclosure may also include other equally effective embodiments.
[0010] Figure 1 This is a schematic cross-sectional view of the energy storage element according to the embodiment.
[0011] Figure 2 This is a schematic cross-sectional view of the double-sided anode electrode according to the embodiment.
[0012] Figure 3 This is a schematic cross-sectional view of the double-sided anode electrode according to the embodiment.
[0013] Figure 4 This is a schematic cross-sectional view of the metal anode shown according to the embodiment.
[0014] Figure 5 This is a flowchart of a method for forming a metal anode according to an embodiment.
[0015] Figures 6A-6F This is a schematic cross-sectional view of the metal anode portion during the formation of the metal anode according to the embodiment.
[0016] Figure 7 This is a schematic diagram of an integrated processing tool for forming a metal anode, according to an embodiment.
[0017] Figure 8 This is a flowchart of a method for forming a metal anode using a transfer substrate, as shown in the embodiment.
[0018] Figures 9A-9B This is a graph of the X-ray photoelectron spectroscopy (XPS) depth profile of an SEI film stack lithium anode sample as shown in the embodiment.
[0019] Figure 10 A modified interface metal anode according to an embodiment is shown.
[0020] For ease of understanding, the same reference numerals have been used to identify the same elements in the figures where possible. It is foreseeable that elements and features of one embodiment may be beneficially incorporated into other embodiments without further explanation. Detailed Implementation
[0021] The following disclosure describes lithium-containing electrodes, high-performance electrochemical devices, such as secondary batteries including the aforementioned lithium-containing electrodes, and methods for manufacturing these devices.
[0022] The many details, dimensions, angles, and other features shown in the figures are merely illustrative of specific embodiments. Therefore, other embodiments may have different details, elements, dimensions, angles, and features without departing from the spirit or scope of this disclosure. Furthermore, further embodiments of this disclosure may be implemented without including the details described below.
[0023] The embodiments described herein will be described with reference to a roller coating system. Other tools capable of performing high-speed deposition processes can also be adapted to benefit from the embodiments described herein. Furthermore, any system capable of implementing the deposition process described herein can be used to benefit. The equipment descriptions herein are for illustrative purposes only and should not be construed as limiting the scope of the embodiments described herein. It should also be understood that, although described as a roller process, the embodiments described herein can also be performed on discrete substrates.
[0024] The development of rechargeable lithium metal batteries is considered a promising technology for achieving high-energy-density energy storage systems. However, current lithium metal batteries are affected by dendrite growth, which hinders their practical application in portable electronic devices and electric vehicles. During several charge / discharge cycles, microscopic lithium fibers called dendrites form and extend on the surface of lithium metal until they contact another electrode. Current flowing through these dendrites can cause a short circuit in the battery. One of the challenges enabling lithium metal battery technology is the development of a stable and efficient solid-state electrolyte interface (SEI). A stable and efficient SEI provides an effective strategy for suppressing dendrite growth, thereby achieving better cycle performance.
[0025] Currently, SEI films are typically formed in situ during battery manufacturing cycles, usually immediately after battery production. During these cycles, when an appropriate potential is established on the anode and a specific organic solvent is used as the electrolyte, the solvent decomposes and forms the SEI film during the first charge. Under typical liquid electrolyte conditions and lower current densities, lithium is deposited, and this growth is attributed to "bottom growth." At higher current densities, the concentration gradient in the electrolyte leads to "tip growth," which can cause a short circuit. Depending on the organic solvent used, the SEI film formed on the anode is typically a mixture of lithium oxide, lithium halide, and hemicarbonate. Initially, the SEI film is electrically insulated but sufficiently conductive for lithium ions. The SEI prevents the electrolyte from decomposing after the second charge. The SEI can be viewed as a three-layer system with two key interfaces. In traditional electrochemical research, it is often referred to as an electrical double layer. In its simplest form, the SEI-coated anode undergoes three stages during charging. These three stages include the anode (M) and the SEI (M2). 0 -ne→M n+ M / SEI Electron transfer between the anode and the SEI interface; migration of cations from the anode-SEI interface to the SEI-electrolyte (E) interface (M). n+ M / SEI →M n+ SEI / E ); and the transfer of cations at the SEI-electrolyte interface (E(solv) + M) n+ SEI / E →M n+ E(solv)).
[0026] A battery's power density and charging rate depend on how quickly the anode energy is released and gains charge. This, in turn, depends on how quickly the anode energy exchanges lithium ions with the electrolyte through the SEI. Lithium-ion exchange at the SEI is a multi-stage process, and as with most multi-stage processes, the overall rate depends on the slowest stage. Anion migration is likely the bottleneck in most systems. Furthermore, the diffusion properties of the solvent may determine the migration rate between the anode-SEI interface and the SEI-electrolyte (E) interface. Therefore, the optimal solvent has low mass to maximize the diffusion rate.
[0027] The specific properties and reactions occurring at the SEI can affect the cycling and capacity of the anode electrode structure. The SEI may thicken during cycling, slowing diffusion from the electrode / SEI interface to the SEI / electrolyte. For example, at high temperatures, alkyl carbonates in the electrolyte decompose into insoluble Li₂CO₃, which can increase the thickness of the SEI film, clog its pores, and restrict lithium-ion access to the anode. SEI growth can also occur through gas escape from the cathode and particle migration to the anode, increasing impedance and reducing capacity. Furthermore, the randomness of lithium metal intercalation into the anode during intercalation can lead to dendrite formation. Over time, these dendrites can puncture the separator, causing short circuits, resulting in overheating, fire, and / or explosion.
[0028] Embodiments of this disclosure relate to the ex-situ construction of a stable and efficient SEI film. The SEI film is formed during the manufacturing process of energy storage devices. This novel and efficient SEI film is believed to suppress the growth of lithium dendrites, thus achieving superior lithium metal cycling performance compared to current lithium-based anodes that rely on in-situ SEI films.
[0029] Figure 1 A cross-sectional view of an energy storage element 100 comprising an anode electrode structure including an SEI membrane stack 140, formed according to embodiments described herein, is shown. In some embodiments, the energy storage element 100 is a rechargeable battery cell. In some embodiments, the energy storage element 100 is combined with other cells to form a rechargeable battery. The energy storage element 100 has a cathode 105, an anode 145, and a separator 130. The cathode 105 includes a cathode current collector 110 and a cathode film 120. The anode 145 includes an SEI membrane stack 140, an anode film 150, and an anode current collector 160. Note that... Figure 1 In the SEI membrane stack 140, the cathode current collector 110, the anode current collector 160, and the separator 130 extend beyond the membrane stack. Although the cathode current collector 110 and the anode current collector 160 do not necessarily need to extend beyond the membrane stack, the portions extending beyond the membrane stack can be used as contacts. The SEI membrane stack 140 can have more than one layer, for example, a membrane composed of lithium carbonate and lithium fluoride (LiF).
[0030] In one embodiment, a portion of the SEI membrane stack 140 is formed by exposing a lithium membrane to SF6 gas to form LiF and Li2S portions of the SEI membrane stack 140 on the surface of the lithium membrane. The SF6 gas can be activated to thermally react with the exposed lithium surface or plasma-activated. The thickness of the SEI membrane stack 140 can be controlled by varying the exposure time and temperature of the SF6 gas.
[0031] Cathode current collector 110 and anode current collector 160, respectively located on cathode film 120 and anode film 150, can be the same or different electronic conductors. Examples of metals that may be included in cathode current collector 110 and anode current collector 160 include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), tin (Sn), silicon (Si), manganese (Mn), magnesium (Mg), alloys thereof, and combinations thereof. In one embodiment, at least one current collector 110 or 160 is porous. Furthermore, the current collector can have any form factor (e.g., metal foil, sheet, or plate), shape, and micro / macro structure. In one embodiment, at least one current collector 110 or 160 comprises a polyethylene terephthalate (“PET”) film covered with a metallic material. In one embodiment, anode current collector 160 is a copper-coated PET film. In another embodiment, anode current collector 160 is a multi-metallic layer located on the PET. This multi-metallic layer can be a combination of copper, chromium, nickel, etc. In one embodiment, the anode current collector 160 is a multilayer structure comprising a copper-nickel coating material. In one embodiment, the multilayer structure includes a nickel or chromium layer as a first layer, a copper layer formed on the first layer as a second layer, and a third layer formed on the second layer comprising nickel, chromium, or both. In one embodiment, the anode current collector 160 is nickel-coated copper. Furthermore, the current collector can have any form factor (e.g., metal foil, sheet, or plate), shape, and micro / macro structure. Typically, in prismatic cells, the contacts are made of the same material as the current collectors and can be formed during the fabrication of the stack or added subsequently. All components, except for the current collectors 110 and 160, contain a lithium-ion electrolyte. In one embodiment, the cathode current collector 110 is aluminum. In one embodiment, the thickness of the cathode current collector 110 ranges from about 0.5 μm to about 20 μm (e.g., from about 1 μm to about 10 μm; from about 5 μm to about 10 μm). In one embodiment, the anode current collector 160 is copper. In one embodiment, the thickness of the anode current collector 160 is from about 0.5 μm to about 20 μm (e.g., from about 1 μm to about 10 μm; from about 2 μm to about 8 μm; from about 5 μm to about 10 μm).
[0032] The anode film 150 or the anode can be any material compatible with the cathode film 120 or the cathode. The energy capacity of the anode film 150 can be greater than or equal to 372 mAh / g, preferably ≥700 mAh / g, and most preferably ≥1000 mAh / g. The anode film 150 can be made of lithium metal, lithium metal foil, or lithium alloy foil (e.g., lithium-aluminum alloy), or a mixture of lithium metal and / or lithium alloy with carbon (e.g., coke, graphite), nickel, copper, tin, indium, silicon, their oxides, or combinations thereof. The anode film 150 typically contains a lithium-containing intercalation compound or a lithium-containing substitution compound. In some embodiments, the anode film 150 contains lithium metal, which can be deposited using the methods described herein. The anode film 150 can be formed by extrusion, physical or chemical thin film techniques, such as sputtering, electron beam evaporation, chemical vapor deposition (CVD), 3D printing, lithium powder deposition, etc. In one embodiment, the thickness of the anode film 150 is between about 0.5 μm and about 20 μm (e.g., between about 1 μm and about 10 μm; between about 5 μm and about 10 μm). In one embodiment, the anode film 150 is a lithium metal or lithium metal alloy film.
[0033] SEI film stack 140 is formed anatomically on anode film 150. SEI film stack 140 is electrically insulating but sufficiently conductive to lithium ions. In one embodiment, SEI film stack 140 is a non-porous membrane. In another embodiment, SEI film stack 140 is a porous membrane. In one embodiment, SEI film stack 140 has a plurality of nanopores with an average pore size or diameter less than about 10 nanometers (e.g., from about 1 nanometer to about 10 nanometers; from about 3 nanometers to about 5 nanometers). In another embodiment, SEI film stack 140 has a plurality of nanopores with an average pore size or diameter less than about 5 nanometers. In one embodiment, SEI film stack 140 has a plurality of nanopores with diameters ranging from about 1 nanometer to about 20 nanometers (e.g., from about 2 nanometers to about 15 nanometers; or from about 5 nanometers to about 10 nanometers).
[0034] SEI film stack 140 can be a coating or a stand-alone layer with a thickness ranging from 1 nanometer to 200 nanometers (e.g., ranging from 5 nanometers to 200 nanometers; ranging from 10 nanometers to 50 nanometers). While not theoretically limited, it is believed that SEI film thicknesses exceeding 200 nanometers may increase resistance within the rechargeable battery.
[0035] Examples of materials that may be included in the SEI film stack 140 include, but are not limited to, chalcogenide films (e.g., CuS, Cu2Se, Cu2S, Cu2Te, CuTe, Bi2Te3, or Bi2Se3 films), or composite chalcogenide films, and may optionally be combined with at least one of the following: lithium carbonate (Li2CO3) films, lithium oxide (Li2O) films, lithium nitride (Li3N) films, and lithium halide films (e.g., LiF, LiCl, LiBr, or LiI). While not theoretically limited, it is believed that the SEI film stack 140 can absorb lithium conductive electrolyte to form a gel during device fabrication, which is beneficial for forming a good solid electrolyte interface (SEI) and helps reduce impedance. Suitable methods for directly depositing portions of the SEI film stack 140 onto a metal film include, but are not limited to, physical vapor deposition (PVD), such as evaporation or sputtering, trench molding processes, thin film transfer processes, or three-dimensional lithium printing processes. Portions of the SEI film stack can be formed by plasma treatment of previously deposited layers (e.g., oxygen plasma treatment of exposed lithium surfaces to form lithium oxide films).
[0036] The cathode film 120 or the cathode itself can be any anode-compatible material, possibly including intercalation compounds, substitution compounds, or electrochemically active polymers. Suitable intercalation materials include, for example, lithium-containing metal oxides, MoS2, FeS2, MnO2, TiS2, NbSe3, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, and V6O. 13 And V₂O₅. Suitable polymers include, for example, polyacetylene, polypyrrole, polyaniline, and polythiophene. The cathode film 120 or cathode can be made of layered oxides, such as lithium cobalt oxide, olivine such as lithium iron phosphate, or spinel such as lithium manganese oxide. Typical lithium-containing oxides can be layered, such as lithium cobalt oxide (LiCoO₂), or mixed metal oxides, such as LiNi. x Co 1-2x MnO2, LiNiMnCoO2 (“NMC”), LiNi 0.5 Mn 1.5 O4, Li(Ni) 0.8 Co 0.15 Al 0.05 O2, LiMn2O4, and doped lithium are rich in layered materials, where x is a zero or non-zero number. Typical phosphates can be fir olivine (LiFePO4) and its variants (e.g., LiFe... (1-x) MgxPO4 (where x is between 0 and 1), LiMoPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3, LiVOPO4, LiMP2O7, or LiFe 1.5P2O7, where x is a zero or non-zero number. Typical fluorophosphates can be LiVPO4F, LiAlPO4F, Li5V(PO4)2F2, Li5Cr(PO4)2F2, Li2CoPO4F, or Li2NiPO4F. Typical silicates can be Li2FeSiO4, Li2MnSiO4, or Li2VOSiO4. Typical non-lithium compounds are NasV2(PO4)2F3. The cathode film 120 can be formed by physical or chemical thin film techniques, such as sputtering, electron beam evaporation, chemical vapor deposition (CVD), etc. In one embodiment, the thickness of the cathode film 120 is from about 10 μm to about 100 μm (e.g., from about 30 μm to about 80 μm; or from about 40 μm to about 60 μm). In one embodiment, the cathode film 120 is a LiCoO2 film. In another embodiment, the cathode film 120 is an NMC film.
[0037] The separator 130 includes a porous (e.g., microporous) polymer substrate capable of conducting ions (e.g., the separator) and having pores. In some embodiments, the porous polymer substrate itself does not need to have ion-conducting capabilities; however, once filled with an electrolyte (liquid, gel, solid, combination, etc.), the combination of the porous substrate and the electrolyte becomes capable of conducting ions. In one embodiment, the porous polymer substrate is a multilayer polymer substrate. In one embodiment, the pores are micropores. In some embodiments, the porous polymer substrate is composed of any commercially available polymer microporous membrane (e.g., single-layer or multilayer), for example, those from Polypore (Celgard Inc., Charlotte, North Carolina), Toray Tonen (Battery Separator (BSF)), SK Energy (Lithium-ion Battery Separator (LiBS)), Evonik Industries (… Ceramic diaphragm), Asahi Kasei (Hipore) TM (polyolefin flat film), DuPont Products manufactured by companies such as [Company Name]. In some embodiments, the porosity of the porous polymer substrate ranges from 20% to 80% (e.g., 28% to 60%). In some embodiments, the average pore size of the porous polymer substrate ranges from 0.02 to 5 micrometers (e.g., 0.08 to 2 micrometers). In some embodiments, the Gurley number of the porous polymer substrate is in the range of 15 to 150 seconds (Gurley number refers to the time required for 10 cc of air to pass through a one square inch membrane under a 12.2-inch column of water). In some embodiments, the porous polymer substrate is polyolefin-based. Exemplary polyolefins include polypropylene, polyethylene, or combinations thereof.
[0038] In some embodiments of the energy storage element disclosed herein, lithium is contained in a metal film of the anode electrode, while the cathode electrode contains lithium manganese oxide (LiMnO4) or lithium cobalt oxide (LiCoO2). For example, although in some embodiments, the anode electrode may also contain a lithium-absorbing material, such as silicon or tin. Even if the energy storage element is planar, it can be formed into a cylindrical shape through a rolled-up stacking method; furthermore, embodiments of this disclosure also contemplate other battery configurations (e.g., prismatic batteries, button batteries).
[0039] The electrolyte immersed in the unit elements (i.e., cathode current collector 110, separator 130, SEI membrane stack 140, and anode current collector 160) can be a liquid / gel or solid polymer, and the composition of each may differ. In some embodiments, the electrolyte primarily comprises a salt and a medium (e.g., in a liquid electrolyte, the medium may be referred to as a solvent; in a gel electrolyte, the medium may be a polymer matrix). The salt may be a lithium salt. Lithium salts may include, for example, LiPF6, LiAsF6, LiCF3SO3, LiN(CF3SO3)3, LiBF6 and LiClO4, lithium bis(trifluoromethanesulfonyl)imide (e.g., LiTFSI), BETTE electrolyte (commercially available from 3M Corporation, Minnesota), and combinations thereof. Solvents may include, for example, ethylene carbonate (EC), propylene carbonate (PC), EC / PC, 2-MeTHF (2-methyltetrahydrofuran) / EC / PC, EC / DMC (dimethyl carbonate), EC / DME (vinyl ether), EC / DEC (diethyl carbonate), EC / EMC (ethyl methyl carbonate), EC / EMC / DMC / DEC, EC / EMC / DMC / DEC / PE, PC / DME, and DME / PC. The polymer matrix may include, for example, PVDF (polyvinylidene fluoride), PVDF:THF (PVDF: tetrahydrofuran), PVDF:CTFE (PVDF: trichlorofluoroethylene), PAN (polyacrylonitrile), and PEO (polyethylene oxide).
[0040] Figure 2 A cross-sectional view of a double-sided anode electrode structure 200 is shown, having solid electrolyte interface (SEI) film stacks 240a and 240b (collectively referred to as 240) formed according to the embodiments described herein. The double-sided anode electrode structure 200 can be used to replace... Figure 1 The anode 145 is shown in the image. SEI film stacks 240a and 240b can be used to replace... Figure 1The SEI film stack 140 is shown in the image. Each SEI film stack 240a, 240b includes a first passivation layer and a second passivation layer. The first passivation layer is located on the anolyte films 150a, 150b. The first passivation layer includes a lithium carbonate layer. The second passivation layer is located on the first passivation layer. The second passivation layer includes a dielectric film. The dielectric film may include lithium halides, such as LiF, LiCl, LiBr, or LiI.
[0041] Figure 3 A cross-sectional view of a double-sided anode electrode structure 300 according to another embodiment is shown, which has a solid electrolyte interface (SEI) film stack 340a, 340b (collectively referred to as 340) formed according to the embodiments described herein. The double-sided anode electrode structure 300 can be replaced with... Figure 1 The anode 145 shown. SEI film stacks 340a and 340b can be used to replace Figure 1 The SEI film stack 140 shown is illustrated. Each SEI film stack 340a, 340b includes a third passivation layer. The third passivation layer includes lithium oxide films 210a, 210b respectively located on each anode film 150a, 150b. Each SEI film stack 340a, 340b further includes a first passivation layer located on the lithium oxide films 210a, 210b. The first passivation layer includes lithium carbonate films 310a, 310b (collectively referred to as 310). Each SEI film stack 340a, 340b further includes a second passivation layer located on the first passivation layer. The second passivation layer includes a dielectric film (e.g., lithium halide films 320a, 320b) (collectively referred to as 320).
[0042] Please note that Figure 2 and Figure 3 In the diagram, the anolyte current collector 160 extends beyond the membrane stack. While the anolyte current collector 160 does not necessarily need to extend beyond the membrane stack, the extended portion can be used as a contact point. Although Figure 2-3 The anode electrode structure shown is depicted as a double-sided electrode structure, but it should be understood that... Figure 2-3 The implementation methods described herein are also applicable to single-sided electrode structures.
[0043] Figure 4An embodiment of the metal anode 400 of the energy storage element 100 is described. The metal anode 400 includes a substrate 460, a metal film 450, and an SEI film stack 440. In one embodiment, the metal film 450 is an anode film 150, and the substrate 460 is an anode current collector 160. In some embodiments, the metal film is a metal film. In some embodiments, the metal film contains a metal or metal alloy, such as lithium. In one embodiment, the metal film 450 is located on a copper substrate 460. In some embodiments, if the anode film 150 is already present on the substrate 460, the metal film 450 is located on the anode film 150. If the anode film 150 is not present, the metal film 450 may be located directly on the substrate 460. Any suitable metal deposition process can be used to deposit the thin film of the metal film 450. The deposition of the metal film 450 can be performed by evaporation, sputtering, trench molding, transfer, or 3D lithium printing. The chamber for depositing the metal thin film may include a PVD system, an electron beam evaporator, a thermal evaporator, a thin film transfer system (including a large-area pattern printing system such as a gravure printing system), or a trench die deposition system. In one embodiment, the thickness of the metal film 450 is less than or equal to 100 micrometers (e.g., from about 1 μm to about 100 μm; from about 3 μm to about 30 μm; from about 20 μm to about 30 μm; from about 1 μm to about 20 μm; or from about 50 μm to about 100 μm). In one embodiment, the thickness of the substrate 402 is between about 10 μm and about 100 μm, for example, about 18 μm.
[0044] The SEI film stack 440 further includes at least one first passivation layer and one second passivation layer. The SEI film stack comprises an electrically insulating (e.g., dielectric material) and ionicly conductive material. In the illustrated embodiment, the first passivation layer is a lithium carbonate (Li₂CO₃) film 310, and the second passivation layer is a lithium halide film 320. The first passivation layer may comprise a lithiophilic material. The first passivation layer may also comprise a dielectric material (e.g., an electrically insulating material). The second passivation layer may comprise a dielectric material (e.g., an electrically insulating material). The lithium halide film may comprise, for example, LiF, LiCl, LiBr, or LiI. In one embodiment, the SEI film stack 440 includes a third passivation layer between the lithium carbonate film 310 and the metal film 450. In one embodiment, the thickness of the lithium carbonate film 310 is about 200 nm or less (e.g., from about 5 nm to about 200 nm; from about 20 nm to about 150 nm; from about 40 nm to about 100 nm; from about 60 nm to about 80 nm). In one embodiment, the thickness of the lithium halide film 320 is about 15 nm or less (e.g., from about 1 nm to about 15 nm; from about 5 nm to about 10 nm; from about 10 nm to about 15 nm). In some embodiments, the first passivation layer and the second passivation layer are not defined layers. For example, the lithium carbonate layer and the lithium halide layer have a mixed region at the interface between lithium carbonate and lithium halide. In embodiments including a third passivation layer, the first passivation layer and the third passivation layer are also not defined layers. For example, the lithium carbonate layer and the lithium oxide layer have a mixed region at the interface between lithium carbonate and lithium oxide.
[0045] A lithium carbonate film 310 is deposited on a metal film 450. In one embodiment, a substrate 460 covered with the metal film 450 is exposed to carbon dioxide (CO2) through a modular gas nozzle. After exposure to CO2, a lithium carbonate film 310 is formed on the metal film 450. A lithium halide film 320 is deposited on the lithium carbonate film 310. The deposition of the lithium halide film 320 can be performed using any of the following methods: sputtering deposition, electron beam evaporation, ion beam deposition, or resistance thermal evaporation. By creating an SEI film stack 440 comprising the lithium halide film 320 and the lithium carbonate film 310, improvements in cell cycle performance, interface characteristics, and electrochemical properties are achieved. Furthermore, as will be discussed further later, the use of lithium halides results in a reduction of lithium oxide in the anode 400.
[0046] Figure 5 This is a flowchart of the method 500 for forming the anode 400 of the aforementioned energy storage element 100, as shown below. Figure 4 As shown. Figures 6A-6F This is a schematic cross-sectional view of the anode 400 during its formation process.
[0047] In operation 502, such as Figure 6AAs shown, a metal film 450 is placed on a substrate 460. In one embodiment, the metal film 450 is an anode film 150, and the substrate 460 is an anode current collector 160. In one embodiment, the substrate 460 is a continuous material plate. The substrate 460 includes any of aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), stainless steel, composite materials, alloys thereof, and combinations thereof. In one embodiment, the substrate 460 is perforated. Furthermore, the substrate 460 can have any form (e.g., metal foil, sheet, or plate), shape, and micro / macro structure.
[0048] The metal film 450 is deposited on the substrate 460 using a flexible substrate coating apparatus 700. Figure 7 The copper substrate 460 is transported via a flexible substrate coating apparatus 700, and lithium is thermally evaporated on the copper substrate 460 to form a metal film 450. In some embodiments, if an anode film 150 already exists on the substrate 460, the metal film 450 is placed on top of the anode film 150. If the anode film 150 is not present, the metal film 450 can be placed directly on the substrate 460. The metal film 450 can be deposited using any suitable metal film deposition process for depositing metal thin films. The deposition of the metal film 450 can be performed by evaporation, sputtering, stencil deposition, transfer deposition, or 3D lithium printing. The chamber used for depositing the metal film 450 may include a PVD system, an electron beam evaporator, a thermal evaporator, a thin film transfer system (including large pattern printing systems such as gravure printing systems), or a stencil deposition system. In one embodiment, the thickness of the metal film 450 is 100 micrometers or less (e.g., from about 1 μm to about 100 μm; from about 3 μm to about 30 μm; from about 20 μm to about 30 μm; from about 1 μm to about 20 μm; or from about 50 μm to about 100 μm).
[0049] In some embodiments, a transfer substrate may be used. This transfer substrate can be a flexible plastic film (e.g., polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polyimide (PI), etc.). In some embodiments, the transfer substrate may be coated with organic or inorganic functional layers that can selectively transfer or assist in the selective transfer of the metal film (e.g., PDMS, boron nitride, alumina (Al₂O₃)). xMaterials such as polytetrafluoroethylene (PTFE), fluorinated ethylene propylene (FEP), perfluorooctanoic acid (PFOA), and polyvinylidene fluoride (PVDF) are used. The metal and dielectric layers are then deposited onto this plastic substrate and subsequently transferred by lamination onto the desired component architecture, such as a current collector or substrate 460 (e.g., copper (Cu) and copper on metallized plastics such as PET). In one embodiment, the thickness of the transfer substrate is 200 micrometers or less, for example, from about 5 micrometers to about 100 micrometers, from about 10 micrometers to about 75 micrometers, or from about 20 micrometers to about 50 micrometers.
[0050] In some embodiments, the substrate 460 is exposed to a pretreatment process, including at least one of plasma treatment or corona discharge process, to remove organic material from the exposed surface of the substrate 460. The pretreatment process is performed before the deposition of a film on the substrate 460.
[0051] In operation 504, an SEI film stack 440 is placed over a metal film 450. The SEI film stack 440 includes a lithium carbonate (Li₂CO₃) film and a lithium halide film. Operation 504 can be further divided into optional operations 506, 508, and 510. Optionally, in operation 506, a lithium oxide (Li₂O) film 210 is placed over the metal film 450. In one embodiment, the thickness of the lithium oxide film 210 is 500 nanometers or less (e.g., from about 1 nm to about 400 nm; from about 25 nm to about 300 nm; from about 50 nm to about 200 nm; or from about 100 nm to about 150 nm). In one embodiment, the lithium oxide film 210 is formed by depositing an additional metal film via PVD in an oxygen-containing atmosphere.
[0052] In operation 508, the first passivation layer is located above the metal film 450, such as Figure 6C As shown. The first passivation layer includes a lithium carbonate film 310. In one embodiment, the thickness of the lithium carbonate film 310 is about 200 nm or less (e.g., from about 5 nm to about 200 nm; from about 20 nm to about 150 nm; from about 40 nm to about 100 nm; from about 60 nm to about 80 nm).
[0053] Selectively, a lithium carbonate (Li₂CO₃) film is positioned above the third passivation layer. The third passivation layer is a lithium oxide film 210, such as... Figure 6DAs shown. In one embodiment, the thickness of the lithium carbonate film 310 is about 200 nm or less (e.g., from about 5 nm to about 200 nm; from about 20 nm to about 150 nm; from about 40 nm to about 100 nm; from about 60 nm to about 80 nm). In one embodiment, the lithium carbonate film 310 is formed by depositing an additional metal film on the lithium oxide film 210 and exposing the metal film 450 to a plasma process (e.g., treatment with a gas of at least one of O2 and CO2) to oxidize the metal film 450. In one embodiment, the lithium oxide film 210 is formed by PVD deposition of an additional metal film in an atmosphere containing oxygen and carbon. In one embodiment, a portion of the lithium oxide film 210 deposited in operation 508 is exposed to a plasma process to form the lithium carbonate film 310.
[0054] In operation 510, such as Figure 6E As shown, a second passivation layer is placed above the lithium carbonate film 310. The second passivation layer includes a dielectric layer, such as a lithium halide film 320. In one embodiment, the lithium halide film is selected from LiF, LiCl, LiBr, and LiI. In one embodiment, the lithium halide film 320 is a lithium fluoride film. In one embodiment, the lithium halide film 320 is deposited on the lithium carbonate film 310 by physical vapor deposition (PVD), evaporation, atomic layer deposition (ALD), trench molding, thin film transfer, or three-dimensional lithium printing. In one embodiment, PVD is a method for depositing the lithium halide film 320. In one embodiment, the lithium halide film 320 is deposited using a thermal evaporation process. In one embodiment, the lithium halide film is formed by reducing a functional layer or surface functional groups on a plastic substrate used for metal deposition. This halide / organic layer will exist on the surface of the metal film 450 after lamination with the substrate 460. In one embodiment, the thickness of the lithium halide film 320 is about 15 nm or less (e.g., from about 1 nm to about 15 nm; from about 5 nm to about 10 nm; from about 10 nm to about 15 nm).
[0055] Optionally, the lithium halide film 320 is located on the lithium carbonate (Li2CO3) film 310, which in turn is located on the lithium oxide film 210, such as... Figure 6FAs shown. In one embodiment, the lithium halide film 320 is deposited on the lithium carbonate film 310 by physical vapor deposition (PVD), evaporation, atomic layer deposition (ALD), trench molding, thin film transfer, or 3D lithium printing. In one embodiment, PVD is the deposition method for the lithium halide film 320. In one embodiment, the lithium halide film 320 is deposited using a thermal evaporation process. In one embodiment, the thickness of the lithium halide film 320 is about 15 nm or less (e.g., from about 1 nm to about 15 nm; from about 5 nm to about 10 nm; from about 10 nm to about 15 nm). During the deposition of the lithium halide film 320 onto the lithium carbonate film 310, the thickness of the lithium oxide film 210 is reduced. In one embodiment, the lithium oxide film 210 is reduced to a thickness so small that it cannot be detected by spectroscopic methods.
[0056] Figure 7 A schematic diagram of a flexible substrate coating apparatus 700 is illustrated, which is used to form an anode electrode structure according to embodiments described herein. According to a typical embodiment, the flexible substrate coating apparatus 700 can be used to manufacture lithium anodes, particularly for an SEI film stack 440 of anode 400. The flexible substrate coating apparatus 700 comprises a roll-to-roll system including an unfolding module 702, a processing module 704, and a winding module 706. In some embodiments, the processing module 704 includes a series of sequentially arranged processing modules or processing chambers 710, 720, 730, and 740, each chamber configured to process a continuous sheet 750 or roll of material. In one embodiment, as... Figure 7 As shown, processing chambers 710-740 are radially arranged around the coating drum 755. Other arrangements are also accepted. For example, in another embodiment, the processing chambers may be placed in a linear arrangement.
[0057] In one embodiment, the processing chambers 710-740 are independent modular processing chambers, each of which is structurally separate from the other modular processing chambers. Therefore, each independent modular processing chamber can be arranged, rearranged, replaced, or maintained independently without affecting each other. Although four processing chambers 710-740 are shown, it should be understood that the flexible substrate coating apparatus 700 can contain any number of processing chambers.
[0058] Processing chambers 710-740 may include any suitable structure, configuration, arrangement, and / or elements enabling the flexible substrate coating apparatus 700 to deposit an anode according to embodiments of the present disclosure. For example, but not limited to, the processing chambers may include a suitable deposition system, including a coating source, power supply, individual pressure control, deposition control system, and temperature control. According to a typical embodiment, the chambers are equipped with independent gas supplies. The chambers are typically separated to provide good gas separation. According to the embodiments described herein, the number of deposition chambers in the flexible substrate coating apparatus 700 is not limited. For example, but not limited to, the flexible substrate coating apparatus 700 may include 3, 6, or 12 processing chambers.
[0059] Processing chambers 710-740 typically include one or more deposition units 712, 722, 732, and 742. Generally, these deposition units can be selected from the group consisting of CVD or ALD sources, PECVD sources, and PVD sources. These deposition units may include an evaporation source and a sputtering source, such as a magnetron sputtering source, a DC sputtering source, an AC sputtering source, a pulsed sputtering source, a radio frequency (RF) sputtering source, or a medium frequency (MF) sputtering source. For example, MF sputtering with a frequency range between 5 kHz and 100 kHz, such as 30 kHz to 50 kHz, can be provided. These deposition units may include an evaporation source. In one embodiment, the evaporation source is a thermal evaporation source or an electron beam evaporation source. In another embodiment, the evaporation source is a lithium (Li) source. Furthermore, the evaporation source may also be an alloy of two or more metals. The material to be deposited (e.g., lithium) can be placed in a crucible. Lithium can be evaporated, for example, by thermal evaporation or electron beam evaporation techniques.
[0060] In some embodiments, any of the processing chambers 710-740 of the flexible substrate coating apparatus 700 may be configured to perform deposition by sputtering, such as magnetron sputtering. As used herein, “magnetron sputtering” refers to sputtering using a magnet assembly, i.e., a unit capable of generating a magnetic field. Typically, such a magnet assembly comprises a permanent magnet. This permanent magnet is usually arranged within a rotatable target or coupled in some way to a planar target such that free electrons are trapped in the magnetic field generated beneath the surface of the rotatable target. Such a magnet assembly may also be arranged coupled to a planar cathode.
[0061] Magnetron sputtering can also be achieved using dual magnetron cathodes, such as, but not limited to, TwinMag. TM Cathode assembly. In some embodiments, the cathodes in the processing chamber are interchangeable. Therefore, a modular design is provided, enabling the apparatus to be optimized for specific manufacturing processes. In some embodiments, the number of cathodes in the chamber is selected to optimize the productivity of the flexible substrate coating apparatus 700.
[0062] In some embodiments, one or more processing chambers 710-740 may be configured to perform sputtering without a magnetron assembly. In some embodiments, one or more chambers may be configured to perform deposition by other methods, such as, but not limited to, chemical vapor deposition, atomic laser deposition, or pulsed laser deposition. In some embodiments, one or more chambers may be configured to perform plasma processing processes, such as plasma oxidation or plasma nitriding processes.
[0063] In some embodiments, processing chambers 710-740 are configured to process both sides of the continuous material sheet 750. Although the flexible substrate coating apparatus 700 is configured to process horizontally oriented continuous material sheets 750, the apparatus can also be configured to process substrates placed in different orientations; for example, the continuous material sheet 750 may be vertically oriented. In some embodiments, the continuous material sheet 750 is a flexible conductive substrate. In some embodiments, the continuous material sheet 750 includes one or more layers formed on the conductive substrate. In some embodiments, the conductive substrate is a copper substrate.
[0064] In some embodiments, the flexible substrate coating apparatus 700 includes a transport mechanism 752. The transport mechanism 752 may comprise any transport mechanism capable of moving a continuous sheet of material 750 through the processing areas of the processing chambers 710-740. The transport mechanism 752 may comprise a universal transport architecture. The universal transport architecture may include a roll-to-roll system having a universal take-up spool 754 located in the winding module 706, a coating drum 755 located in the processing module 704, and a feed spool 756 located in the unfolding module 702. The take-up spool 754, coating drum 755, and feed spool 756 can be individually heated. The take-up spool 754, coating drum 755, and feed spool 756 can be individually heated using a heat source located inside each spool or an external heat source. The universal transport architecture may further include one or more auxiliary transport spools 753a, 753b located between the take-up spool 754, coating drum 755, and feed spool 756. Although the flexible substrate coating apparatus 700 is shown as having a single processing area, in some embodiments, it may be advantageous to have separate or independent processing areas for each individual processing chamber 710-740. For embodiments with independent processing areas, modules, or chambers, the general transport architecture may be a roll-to-roll system, wherein each chamber or processing area has an independent take-up roll and a feed roll, and one or more optional intermediate transport rolls located between the take-up roll and the feed roll.
[0065] The flexible substrate coating apparatus 700 may include a feed spool 756 and a take-up spool 754 to move a continuous material sheet 750 through different processing chambers 710-740. In one embodiment, the first processing chamber 710 and the second processing chamber 720 are each configured to deposit a portion of a metal film. The third processing chamber 730 is configured to deposit a lithium carbonate film. The fourth processing chamber 740 is configured to deposit a lithium halide film on the lithium carbonate film. In another embodiment, when the continuous material sheet 750 is a polymer material, the first processing chamber 710 is configured to deposit a copper film on the polymer material. The second processing chamber 720 is configured to deposit a portion of a metal film. The third processing chamber 730 is configured to deposit a lithium carbonate film. The fourth processing chamber 740 is configured to deposit a lithium halide film. In some embodiments, the finished negative electrode may not be collected on the take-up spool 754 as shown, but may be directly integrated with the insulator and positive electrode, etc., to form a battery cell.
[0066] In one embodiment, processing chambers 710-720 are configured to deposit a thin film of lithium metal on a continuous material sheet 750. The lithium metal film can be deposited using any suitable lithium deposition process for depositing lithium metal films. The deposition of the lithium metal film can be accomplished using PVD processes, such as evaporation, molding, transfer, lamination, or 3D lithium printing. The chambers for depositing the lithium metal film may include PVD systems, such as electron beam evaporators, thin film transfer systems (including large-area patterning systems such as gravure printing systems), lamination systems, or molding deposition systems.
[0067] In one embodiment, the third processing chamber 730 is configured to deposit a lithium carbonate film on a metal film. The lithium carbonate film can be deposited using the PVD sputtering technique described herein. In one embodiment, the fourth processing chamber 740 is configured to form a lithium halide film on the lithium carbonate film. A suitable lithium deposition process for depositing lithium metal thin films can be used to deposit the lithium metal thin film. The deposition of the lithium metal thin film can be accomplished by a PVD process, such as evaporation, trench molding, transfer, lamination, or 3D lithium printing. In one embodiment, the fourth processing chamber 740 is an evaporation chamber or a PVD chamber configured to deposit a lithium halide film on a continuous material sheet 750. In one embodiment, the evaporation chamber has a processing area that may contain an evaporation source placed in a crucible, which may be a thermal evaporator or an electron beam evaporator (cold), for example, in a vacuum environment.
[0068] During operation, a continuous sheet of material 750 unfolds from a feed reel 756, indicated by the substrate movement direction shown by arrow 708. The continuous sheet of material 750 can be guided by one or more auxiliary transfer reels 753a, 753b. Alternatively, the continuous sheet of material 750 may be guided by one or more substrate guiding control units (not shown), which control the correct operation of the flexible substrate, for example, by fine-tuning the orientation of the flexible substrate.
[0069] After being unwound from the feed reel 756 and passed through the auxiliary transfer reel 753a, the continuous material sheet 750 is then moved through the deposition area provided by the coating drum 755, which corresponds to the positions of the deposition units 712, 722, 732, and 742. During operation, the coating drum 755 rotates about axis 751, causing the flexible substrate to move in the direction of arrow 708.
[0070] Figure 8 This is a flowchart of a method for forming a lithium metal anode 400 using a transfer substrate. In operation 802, a second passivation layer is placed over the transfer substrate (not shown). The second passivation layer comprises a dielectric film, such as a lithium halide film 320. In one embodiment, the lithium halide film 320 is selected from LiF, LiCl, LiBr, and LiI. In one embodiment, the lithium halide film 320 is a lithium fluoride film. In one embodiment, the lithium halide film 320 is deposited onto the transfer substrate by physical vapor deposition (PVD), evaporation, atomic layer deposition (ALD), trench molding, thin film transfer, or three-dimensional lithium printing. In one embodiment, PVD is a method for depositing the lithium halide film 320. In one embodiment, the lithium halide film 320 is deposited using a thermal evaporation process. In one embodiment, the lithium halide film is formed by reducing a functional layer or surface functional groups on a plastic substrate for metal deposition. This halide / organic layer will then appear on the surface of the metal film 450 after being laminated to a substrate 460. In one embodiment, the thickness of the lithium halide film 320 is about 15 nm or less (e.g., from about 1 nm to about 15 nm; from about 5 nm to about 10 nm; from about 10 nm to about 15 nm).
[0071] The transfer substrate can be a flexible plastic film (e.g., polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polyimide (PI), etc.). In some embodiments, the transfer substrate may be coated with one or more organic or inorganic functional layers, which can selectively transfer or assist in the selective transfer of metal films (e.g., PDMS, boron nitride, alumina (Al₂O₃)). xMaterials used include polytetrafluoroethylene (PTFE), fluorinated ethylene propylene (FEP), perfluorooctanoic acid (PFOA), and polyvinylidene fluoride (PVDF). Subsequently, metal and dielectric layers are deposited onto this plastic substrate and transferred by lamination to the desired component architecture, such as a current collector or substrate 460 (e.g., copper (Cu) and copper on metallized plastics such as PET). In one embodiment, the thickness of the transfer substrate is 200 micrometers or less, for example, from about 5 micrometers to about 100 micrometers, from about 10 micrometers to about 75 micrometers, or from about 20 micrometers to about 50 micrometers.
[0072] In operation 804, a first passivation layer is disposed over a second passivation layer. The first passivation layer includes a lithium carbonate film 310. In one embodiment, the thickness of the lithium carbonate film 310 is about 200 nm or less (e.g., from about 5 nm to about 200 nm; from about 20 nm to about 150 nm; from about 40 nm to about 100 nm; from about 60 nm to about 80 nm). In one embodiment, the thickness of the lithium carbonate film 310 is about 200 nm or less (e.g., from about 5 nm to about 200 nm; from about 20 nm to about 150 nm; from about 40 nm to about 100 nm; from about 60 nm to about 80 nm).
[0073] In optional operation 806, a third passivation layer is placed over the first passivation layer. The third passivation layer comprises a lithium oxide film. In one embodiment, the lithium oxide film 210 is formed by depositing an additional metal film via PVD in an oxygen- and carbon-containing atmosphere. The thickness of the lithium oxide film 210 is 500 nanometers or less (e.g., about 1 nm to about 400 nm; about 25 nm to about 300 nm; about 50 nm to about 200 nm; or about 100 nm to about 150 nm). The lithium oxide film 210 is formed by depositing an additional metal film via PVD in an oxygen-containing atmosphere.
[0074] In operation 808, a metal film 450 is placed over a first passivation layer. In one embodiment, the metal film 450 is an anode film 150. Alternatively, the metal film may be placed over a lithium oxide film 210. The deposition of the metal film 450 can be performed by evaporation, sputtering, trenching, transfer, or 3D lithium printing. The chamber for depositing the metal film 450 may include a PVD system, an electron beam evaporator, a thermal evaporator, a thin film transfer system (including large-pattern printing systems, such as gravure printing systems), or a trenching deposition system. In one embodiment, the thickness of the metal film 450 is 100 micrometers or less (e.g., about 1 μm to about 100 μm; about 3 μm to about 30 μm; about 20 μm to about 30 μm; about 1 μm to about 20 μm; or about 50 μm to about 100 μm).
[0075] In operation 810, a film (e.g., a first passivation layer, a second passivation layer, a third passivation layer, and a metal film) is transferred from the transfer substrate to the substrate 460. In one embodiment, the substrate 460 is an anodic current collector 160. In one embodiment, the substrate 460 is a continuous sheet of material. The substrate 460 includes any of aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), stainless steel, cladding materials, alloys thereof, and combinations thereof. In one embodiment, the substrate 460 is perforated. Furthermore, the substrate 460 can have any form (e.g., metal foil, sheet, or plate), shape, and micro / macro structure.
[0076] In some embodiments, the substrate 460 is exposed to a pretreatment process, which includes at least one of plasma treatment or corona discharge process, to remove organic material from the exposed surface of the substrate 460. The pretreatment process is performed before the film is deposited on the substrate 460.
[0077] Implementation
[0078] The following non-limiting embodiments are used to further illustrate the embodiments described herein. However, these embodiments are not intended to cover all situations, nor are they intended to limit the scope of the embodiments described herein.
[0079] A flexible substrate coating apparatus is used for thermally evaporating metal films with thicknesses ranging from about 1 μm to about 20 μm, depositing them onto a foil substrate with a thickness of about 6 μm to about 18 μm. The metal film may include a lithium metal film. Lithium is evaporated from a crucible maintained at about 650°C. The evaporation rate is monitored by a quartz crystal oscillator and maintained at... The foil is wound at a speed of approximately 0.1 m / min to approximately 10 m / min. After metal film deposition, the lithium-coated substrate is exposed to carbon dioxide (CO2) gas through a modular gas nozzle, resulting in the formation of a lithium carbonate film with a thickness ranging from approximately 5 nm to approximately 20 nm. The coated roll is removed from the flexible substrate coating apparatus and cut into 15 cm x 20 cm A5-type samples and placed in a sample holder. The prepared samples are then transferred to a tool kit.
[0080] This toolkit supports resistive thermal evaporation, sputtering deposition, electron beam evaporation, and ion-assisted deposition processes. Lithium halide films are grown on lithium metal-coated substrates and on silicon wafers via thermal evaporation. The substrate temperature is maintained at a constant approximately 25°C during deposition. The starting material is ultra-high purity single-crystal lithium halide powder, which is heated to approximately 800°C in an aluminum oxide crucible. The evaporation rate, monitored by a quartz oscillator, is maintained at... The vapor pressure within the deposition chamber was maintained below 1 mPa. The thickness of the lithium halide samples ranged from approximately 1 nm to approximately 200 nm.
[0081] The composition of the SEI film stack was characterized using X-ray photoelectron spectroscopy (XPS). Samples were sputtered in argon plasma to produce a compositional depth profile. The results confirmed the presence of a pure lithium halide film with minimal contaminants. Both the lithium carbonate and lithium halide films exhibited low oxide and hydroxide contents, such as... Figure 9A and 9B As shown, this contrasts sharply with lithium metal without an SEI membrane stack, which continuously reacts with contaminants, leading to the formation of hydroxide and oxide coatings. The SEI membrane stack effectively stabilizes the lithium metal interface and significantly limits contamination and coating formation by undesirable oxides and hydroxides.
[0082] The effectiveness of the SEI membrane stack was investigated by exposing the lithium metal anode to an uncontrolled environment outdoors in a dry setting with relatively high levels of moisture, oxygen, and nitrogen. Lithium retained its silvery appearance because the SEI membrane stack protected it from reaction and exposure. Non-SEI membrane stack anodes, however, failed to maintain their appearance and turned black. Nevertheless, the SEI membrane stack anodes remained in good condition after 5 minutes of exposure. Therefore, it is clear that non-SEI membrane stack anodes exhibited accelerated oxidation in a dry outdoor environment compared to SEI membrane stack anodes.
[0083] A coin battery containing modified lithium on copper was fabricated (5μm lithium, 18μm copper, 1cm). 2 The electrolyte consisted of a dual polymer separator (Celgard 2400) and 60 μL of 1M LiPF6 with 2% FEC in a 1:1 EC:EMC ratio. Static electrochemical impedance spectroscopy (PEIS) was performed at 5 mV 2 hours after battery assembly, with a frequency range from approximately 1 MHz to approximately 10 mHz. DC internal resistance (DCIR) measurements were performed over currents ranging from approximately 0.2 mA to approximately 3 mA in 0.2 mA increments. Each current pulse lasted 10 seconds, with a 15-minute rest period between pulses. The battery was cycled for 15 minutes at 2 mA per charge / discharge cycle, with a cutoff voltage set to 1 V. At least five batteries were tested for all tests to provide statistical distribution.
[0084] Figure 10A modified interface lithium metal anode 1000 is described. The modified interface lithium metal anode 1000 includes a separator 1030, a first passivation layer 1010a on one side, a second passivation layer 1010b on one side, a second passivation layer 1020a on one side, a second passivation layer 1020b on one side, a metal film 1060a on one side, and a metal film 1060b on the other side. The first and second passivation layers 1010a and 1010b are located on the first and second sides of the separator 1030, respectively. The second passivation layers 1020a and 1020b on the first and second sides are located on the first and second passivation layers 1010a and 1010b, respectively. The metal films 1060a and 1060b on the first and second sides are located on the second passivation layers 1020a and 1020b, respectively. The lithium carbonate / lithium halide SEI film stack is directly deposited onto lithium metal via PVD and then used in a deposition-stripping cycle.
[0085] When describing elements of this disclosure or its exemplary aspects or embodiments, the terms "a," "an," and "the" are intended to mean one or more of the element.
[0086] The terms “include,” “contain,” and “have” are intended to be inclusive, meaning that other elements may be included in addition to those listed.
[0087] While the above description pertains to embodiments of this disclosure, other further embodiments may be designed without departing from its basic scope, the scope of which is defined by the following claims.
Claims
1. An anode for a battery, the anode comprising: a substrate; a metal film on the substrate, wherein the metal film comprises a metal or a metal alloy; and a film stack on the metal film, the film stack comprising: a first passivation layer on the metal film, wherein the first passivation layer has a lithium affinity; and a second passivation layer on the first passivation layer; wherein the film stack is electrically insulating and ionically conductive.
2. The anode of claim 1, wherein the metal film comprises lithium.
3. The anode of claim 1, wherein the film stack is a solid-state electrolyte interphase film.
4. The anode of claim 1, wherein the first passivation layer is a lithium carbonate film.
5. The anode of claim 1, wherein the second passivation layer is a dielectric film.
6. The anode of claim 1, further comprising a third passivation layer on the metal film, wherein the first passivation layer is on the third passivation layer.
7. The anode of claim 6, wherein the third passivation layer is a lithium oxide film.
8. An energy storage element, the energy storage element comprising: a cathode, the cathode comprising: a cathode current collector; a cathode film on the cathode current collector; a separator film on the cathode film; and an anode on the separator film, the anode comprising: an anode film on the separator film; a film stack on the anode film, the film stack comprising: a first passivation layer on the anode film, wherein the first passivation layer has a lithium affinity; and a second passivation layer on the first passivation layer, wherein the film stack is electrically insulating and ionically conductive; and an anode current collector on the anode film, wherein the anode comprises a metal or a metal alloy.
9. The energy storage element of claim 8, wherein the anode current collector is a substrate.
10. The energy storage element of claim 8, wherein the anode film is a metal film.
11. The energy storage element of claim 8, wherein the first passivation layer is a lithium carbonate film.
12. The energy storage element of claim 8, wherein the second passivation layer is a dielectric film.
13. The energy storage element of claim 8, further comprising a third passivation layer on the anode film, wherein the first passivation layer is on the third passivation layer.
14. The energy storage element of claim 13, wherein the third passivation layer is a lithium oxide film.
15. A method of forming an anode for a battery, the method comprising: placing a metal film on a substrate, wherein the metal film comprises a metal or a metal alloy; and placing a film stack on the metal film, the placing of the film stack comprising: placing a first passivation layer on the metal film, wherein the first passivation layer is lithium affinity; and placing a second passivation layer over the first passivation layer, wherein the stack of films is electrically insulating and ionically conductive.
16. The method of claim 15, wherein placing the second passivation layer is performed using physical vapor deposition, evaporation deposition, atomic layer deposition, slot-die process, thin film transfer process, or three-dimensional lithium printing process.
17. The method of claim 15, wherein placing the first passivation layer is performed by exposing the metal film to carbon dioxide.
18. The method of claim 15, further comprising: placing a third passivation layer over the metal film, wherein the first passivation layer is positioned over the third passivation layer.
19. The method of claim 18, wherein placing the third passivation layer is performed using physical vapor deposition.
20. The method of claim 15, further comprising: placing a separator film over the stack of films; and placing a cathode over the separator film, the placing the cathode comprising: placing a cathode film over the separator film; and placing a cathode current collector over the cathode film.
